English songs for enhancing university students’ pronunciation: A qualitative case study - Dian Sri Mulyani; Endang Darsih; Siti Hafsah Setiorini; Fauziah Fauziah; Gita Octapiani; Tiara Eriani (JEIT (Journal of Educational Innovations and Technologies), 2026)
This study investigates how university students utilize English songs to enhance their English pronunciation skills, explores their perceptions of English songs as a learning medium, and identifies the benefits and challenges they experience in this learning process. Using a qualitative case study design, semi-structured interviews were conducted with 15 undergraduate students majoring in English Language Education at an Kuningan university. The data were analyzed using thematic analysis to identify recurring themes and patterns within the participants’ responses. The findings reveal that students employ diverse strategies when using English songs for pronunciation learning, including repeated listening, lyric-reading while listening, dictionary and IPA reference checking, and applying learned pronunciation patterns in daily conversations. Participants expressed generally positive perceptions, describing the experience as enjoyable, engaging, and less intimidating compared to formal classroom instruction. Students reported improvements in word pronunciation, intonation, rhythm awareness, vocabulary development, and speaking confidence. However, they also identified notable challenges, including fast song tempo, unclear or connected speech in lyrics, unfamiliar vocabulary, and accent variation among different artists. The study suggests that English songs serve as a valuable supplementary tool for pronunciation learning when integrated with structured instructional support and additional learning resources.